How is The Grammatical Relation of Batak Toba Wedding Ceremony? - Usman Sidabutar; Mulyadi Mulyadi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This article discusses grammatical relations in Toba Batak language. Toba Batak language has formal markings, both predicates and arguments that show the relationship between clause elements, and the coding of words in the language. arguments are integrated syntactically. This research uses descriptive qualitative research. Qualitative is used to investigate an issue in order to gain a clear understanding of a particular phenomenon. The main data of this research are sentences. Sentence data in this study were obtained through traditional Toba Batak documents, namely 'marhata sinamot' which is commonly used Grammatical relations have an important role and function to identify the correctness of the syntactic process because they are considered to connect arguments with clauses. The grammatical relationship and the semantic role of the Toba Batak language are S = A/P and S = P/A. That is, the Toba Batak language treats S as A and S as P. A language is said to be of ergative type if the patient (P) of a transitive verb is treated with or coreferential with the subject (S) in an intransitive clause and different from the agent (A) of the verb transitive.